Exploring the integration of sustainable urban mobility strategies into master plans: an analysis of the cities of Várzea Paulista and Indaiatuba - Barduco, Julia Matiko; Cavalcante, José Davi dos Santos Silva; Magagnin, Renata Cardoso (Latin American Journal of the Built Environment & Sustainability, 2025)
Objective – To investigate the extent to which the master plans of Várzea Paulista and Indaiatuba (SP) incorporate sustainable urban mobility strategies aligned with the goals of the 2030 Agenda, examining the connection between Urban Planning, Territorial Equity, and the Sustainable Development Goals (SDGs).Methodology – The master plans were evaluated using a qualitative and descriptive approach, based on parameters defined by Magagnin (2023), supplemented by others established by the authors from different bibliographic references. The evaluation was organized into four axes: i) General characterization of the plan, ii) Identification of themes relevant to urban mobility policy, iii) Alignment with the Sustainable Development Goals (SDGs), and iv) Intersectoral and Regional Integration.Originality/Relevance – The study highlights the incorporation of themes and indicators related to urban mobility, linked to urban planning, the SDGs, and Intersectoral and Regional Integration.Results – Both master plans present principles of sustainable urban mobility. However, Indaiatuba shows greater detail and integration among urban planning tools, monitoring, intersectoral policies, and global commitments. Várzea Paulista, on the other hand, adopts a more generic and dispersed approach.Theoretical/Methodological Contributions – Methodologically, it expands the understanding of how to articulate sustainable mobility indicators in urban planning instruments.Social and Environmental Contributions – The integration between mobility, territorial equity, and sustainability can reduce inequalities in access to services and opportunities. Environmentally, prioritizing active modes and public transport contributes to reducing emissions and to a more sustainable use of land and natural resources.
Keywords: Master Plan; Sustainable urban mobility; Sustainable Development Goals